Analysis of Vibration Characteristics of Hydraulic Excavator Device Under Flat Ground Conditions - Kailei Liu; Haifang Zhong; Maoze Chen; Jing Yang; Hongbin Qiang; Shaopeng Kang (Modelling and Simulation in Engineering)
Hydraulic excavators, characterized by their high efficiency and versatility, are crucial equipment in engineering construction. During the automatic excavation process, the excavator may experience resonance phenomena, which can affect the stability of the entire system. In order to study the vibration harmonic response of the excavator arm in the process of reciprocating motion, firstly, the model of the excavator arm is designed in three-dimensional software, and the finite element meshing software is used to perform hexahedral meshing of the excavator arm model and define the material properties. Secondly, the modal analysis of the excavator arm is carried out by finite element simulation software, and the displacement and acceleration harmonic response analysis is carried out using the modal superposition method. Finally, the vibration experiment of reciprocating motion with different frequencies is carried out on the experimental platform of the excavator arm. The simulation and experimental results show that the maximum value of the displacement and acceleration response of the excavator arm corresponds to the frequency near the second-order intrinsic frequency, and the excavator arm is greatly affected by the second-order intrinsic frequency; controlling the frequency of the reciprocating motion of the hydraulic cylinder within 13 Hz can effectively avoid the resonance phenomenon of the excavator arm device.